Unkempt Is Negatively Regulated by mTOR and Uncouples Neuronal Differentiation from Growth Control. - Avet-Rochex, A.; Carvajal, N.; Christoforou, C.P.; Yeung, K.; Maierbrugger, K.T.; Hobbs, C.; Lalli, G.; Cagin, U.; Plachot, C.; McNeill, H.; Bateman, J.M. (PLoS Genetics, 2014)
Neuronal differentiation is exquisitely controlled both spatially and temporally during nervous system development. Defects in the spatiotemporal control of neurogenesis cause incorrect formation of neural networks and lead to neurological disorders such as epilepsy and autism. The mTOR kinase integrates signals from mitogens, nutrients and energy levels to regulate growth, autophagy and metabolism. We previously identified the insulin receptor (InR)/mTOR pathway as a critical regulator of the timing of neuronal differentiation in the Drosophila melanogaster eye. Subsequently, this pathway has been shown to play a conserved role in regulating neurogenesis in vertebrates. However, the factors that mediate the neurogenic role of this pathway are completely unknown. To identify downstream effectors of the InR/mTOR pathway we screened transcriptional targets of mTOR for neuronal differentiation phenotypes in photoreceptor neurons. We identified the conserved gene unkempt (unk), which encodes a zinc finger/RING domain containing protein, as a negative regulator of the timing of photoreceptor differentiation. Loss of unk phenocopies InR/mTOR pathway activation and unk acts downstream of this pathway to regulate neurogenesis. In contrast to InR/mTOR signalling, unk does not regulate growth. unk therefore uncouples the role of the InR/mTOR pathway in neurogenesis from its role in growth control. We also identified the gene headcase (hdc) as a second downstream regulator of the InR/mTOR pathway controlling the timing of neurogenesis. Unk forms a complex with Hdc, and Hdc expression is regulated by unk and InR/mTOR signalling. Co-overexpression of unk and hdc completely suppresses the precocious neuronal differentiation phenotype caused by loss of Tsc1. Thus, Unk and Hdc are the first neurogenic components of the InR/mTOR pathway to be identified. Finally, we show that Unkempt-like is expressed in the developing mouse retina and in neural stem/progenitor cells, suggesting that the role of Unk in neurogenesis may be conserved in mammals.